Combined examination of glyceryl trinitrate‐mediated vascular dilation with flow‐mediated vascular dilation is essential for assessment of vascular function in type 2 diabetes. Issue 3 (11th December 2012) - Furuta, Machi; Ueyama, Minoru; Morita, Shuhei; Yamana, Akiko; Sanke, Tokio
Abstract Aims/Introduction In order to characterize the impaired vascular function in type 2 diabetes (DM) patients, we evaluated the flow‐mediated vascular dilation (FMD) with glyceryl trinitrate‐mediated vascular dilation (NMD) using ultrasonography. Materials and Methods A total of 111 DM patients and 42 healthy control participants were studied. The maximal dilatation of FMD and NMD (%FMD and %NMD, respectively), the beginning time (T) of dilatation after stimulation and the velocity (V) of the vascular dilatation were also measured. Results Among DM patients, 49% had impaired %NMD, which affects the results of %FMD. In DM patients with normal %NMD, the %FMD was also significantly lower than that in control participants, although the T and the V were not impaired. In contrast, both the T and the V were disturbed in the DM patients with low %NMD. Multiple linear regression analysis showed that %NMD was independently correlated with albuminuria. Our results indicate that the impaired FMD in DM is be affected by low NMD, and impaired endothelial function already exists even in DM patients whose vascular smooth muscle function is still retained, and also albuminuria is the clinical feature of DM with low %NMD. Conclusions Examination of NMD, not only FMD, should be carried out as it offers the possibility of clarifying vascular function in DM patients.